Hierarchical structure control in solution spinning for strong and multifunctional carbon nanotube fibers. (30th August 2022) - Kim, Seo Gyun; Choi, Gyeong Min; Jeong, Hyeon Dam; Lee, Dongju; Kim, Sungyong; Ryu, Ki-Hyun; Lee, Suhun; Kim, Jungwon; Hwang, Jun Yeon; Kim, Nam Dong; Kim, Dae-Yoon; Lee, Heon Sang; et al.
Abstract: Many strategies for manufacturing high-performance carbon nanotube (CNT) fibers have been reported in the past decade. Although spinning is an essential process regardless of the CNT pre-treatment method or fiber post-treatment route, little research has been carried out into the spinning process itself. During the formation of such fibers through the spinning, intra- and inter-bundle voids inevitably arise. The size and amount of these voids determines the macroscopic properties of fibers. Therefore, controlling the internal voids of fibers is key for enhancing their macroscopic properties. We systematically explore changes in the microstructures of fibers, especially inter- and intra-bundle voids in the solution spinning. Around the spinneret of the exit, extensional deformation by drawing is key for fiber orientation, and we find the minimum draw ratio ( D R ∗ = 4.5 ) for target orientation of the fiber. Moreover, by controlling the coagulation process, the shape of the fiber is made close to a circular shape, which drastically reduces voids in the fiber to 0.08 vol%. Consequently, the increase in packing density and orientation maximizes the fiber properties. The resulting fibers, which were highly oriented and exhibited a fine morphology, have the tensile strength of 5.0 ± 0.3 GPa, modulus of 302 ± 31 GPa, electrical conductivity of 11.2 ± 0.5 MS m −1, thermal conductivity of 398 ± 27 W m −1  K −1, and knot efficiency of 85 ± 11%. We believe that this systematic investigation of fiber formation provides useful insights into the development of high-performance multifunctional CNT fibers. Graphical abstract: Image 1 Highlights: The microstructural changes of fibers are explored in solution spinning. Extensional deformation by drawing is the most important for fiber orientation. Coagulation is the main process that controls the internal voids in the fiber. The circular shape of the fiber dramatically reduces the void defects in the fiber. Voids control in fibers is the key to improving the macroscopic properties.